Designing an Interactive Learning Game BUDIAN Based on Culture and Arts with a Design Thinking Approach - Muhammad Isfa' Lana; Jaka Septiadi; Rizki Hikmawan; Rani Yuniar; Nabiilah Lintang Dadari (FKIP - Universitas Riau, 2026)
The purpose of this research is to develop an interactive learning application design, BUDIAN, to expand access to arts and culture learning and address the limitations of arts facilities in schools. The research used the Research and Development (R&D) method with a Design Thinking approach through the stages of empathize, define, ideate, prototype, and test. The development results showed that the initial trial on 13 respondents resulted in an average feature access time of 234.1 seconds and several inputs related to navigation, which were then improved in the revision stage. Further testing using the System Usability Scale (SUS) on 25 respondents showed an average score of 84.3 (Excellent category), indicating the application has a high level of usability. This research has an impact on the availability of interactive, contextual, and user-centered cultural learning application designs, and fills the gap in previous research by comprehensively documenting the integration of Design Thinking in R&D. The BUDIAN application has the potential to increase cultural literacy and support the preservation of Indonesian culture through innovative digital media.